Análisis doctrinario de los sistemas de control de constitucionalidad y su aplicación en el Ecuador - Arévalo Carrillo, María Ligia (2023)
The present research is based on the doctrinal study of the systems of control of constitutionality and its application in Ecuador, this being a transcendental topic in the academy, because it has been the subject of several legal debates, both by treatises specialized in constitutional matters, as well as by the Constitutional Court of Ecuador itself, these indeterminations between the control of constitutionality and the principle of direct application of the Constitution have caused some confusion as to what type of control of constitutionality is identified in the Ecuadorian legal system and the delimitation that this has with the principle of direct application of the Constitution. Therefore, this work is oriented to determine through the doctrinal study of the systems of control of constitutionality, the model of control of constitutionality that is recognized in the Constitution of 2008, to achieve this objective, this work develops in its theoretical framework the concepts and definitions related to the system of control of constitutionality. Likewise, it is studied from a critical perspective, the evolution that this system has had in the history of constitutionalism and finally in the Ecuadorian context. In order to achieve this purpose, the analytical deductive method has been mainly used, because it will begin with the normative analysis and the jurisprudence issued by the Constitutional Court regarding constitutional control and the principle of direct application of the Constitution. Likewise, it will be noted that there is a lack of knowledge in relation to the scope of the control of constitutionality and the principle of direct application of the Constitution, according to the results obtained from the survey and interview technique, therefore it is intended to understand the particularities that delimit both legal institutions. Finally, the study carried out through the technique of surveys, interviews, analysis of cases and statistical data shows that there is a certain lack of knowledge on the part of the operators of ordinary justice with respect to the moment of direct application of the Constitution and when they must submit a norm to the Constitutional Court for consultation, despite the fact that the jurisprudence of the constitutional magistracy has established the parameters to be followed by the judges of instance in order for the consultation to be admitted, developing the scope of article 142 of the Organic Law of Jurisdictional Guarantees and Constitutional Control.